Perdas de nutrientes por erosão e sua distribuição espacial em área sob cana-de-açúcar - Izidorio, Ricardo [UNESP]; Martins Filho, Marcílio Vieira [UNESP]; Marques Júnior, José [UNESP]; Souza, Zigomar M. de; Pereira, Gener Tadeu [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2005)
O presente trabalho teve como objetivo principal determinar as perdas de nutrientes por erosão em entressulcos, sulcos e global (entressulcos + sulcos, A), em área cultivada com cana-de-açúcar submetida à queima da palhada na sua pré-colheita, na Fazenda Santa Bárbara, localizada em Guariba - SP, sob um Latossolo Vermelho eutroférrico (LVef). Parcelas experimentais foram submetidas à chuva simulada com intensidade de 80 mm h-1, durante 65 minutos. Análises do sedimento erodido indicaram altas taxas de enriquecimento: 1,62 (matéria orgânica, MO); 4,30 (P); 1,17 (K); 1,33 (Ca) e 1,24 (Mg) vezes em relação ao solo original. As perdas de solo e nutrientes, em função do tipo de erosão, obedeceram à seguinte ordem: sulcos > global > entressulcos. Análises geoestatísticas indicaram que as perdas de solo (A), MO, P, K e Ca por erosão apresentaram forte grau de dependência espacial, enquanto as perdas de Mg tiveram moderado grau de dependência espacial. Mapas da distribuição dos padrões de variabilidade espacial das perdas por erosão indicaram que o cultivo de cana-de-açúcar conserva as propriedades químicas e físicas do solo na maior parte da área.

The principal objective of this study was to determine the nutrient losses from interrill, rill and global erosion (interrill + rill, A) in an area cultivated with sugarcane at Santa Bárbara farm, in the region of Guariba (SP), in a Typic Haplustox, very clayey texture. The cane was burnt prior to harvest. The plots were submitted to a rainfall simulation at intensity of approximately 80 mm h-1 for about 65 minutes. Analyses of the sediment indicated much higher enrichment ratio: 1.62 (organic matter, OM); 4.30 (P); 1.17 (K); 1.33 (Ca) and 1.24 (Mg) times when compared with the original soil. The nutrients and the soil losses in function of the erosion type have the following order: rill > interrill > large plots. Geostatistical analyses indicated that the soil erosion (A) and OM, P, K e Ca losses have a strong spatial dependence degree, while Mg losses have a moderate spatial dependence degree. Distribution maps showing spatial patterns variability of the erosion losses indicated that sugarcane culture conserves the soil chemical and physical properties in the greatest part of the area.
Nutrient losses by erosion and spatial distribution in area cultivated with sugarcane
Keywords: interrill erosion; rill erosion; Geostatistics; erosão em entressulcos; erosão em sulcos; Geoestatística